2016
DOI: 10.1158/1940-6207.capr-15-0377
|View full text |Cite
|
Sign up to set email alerts
|

Gene Methylation and Cytological Atypia in Random Fine-Needle Aspirates for Assessment of Breast Cancer Risk

Abstract: Methods to determine individualized breast cancer risk lack sufficient sensitivity to select women most likely to benefit from preventive strategies. Alterations in DNA methylation occur early in breast cancer. We hypothesized that cancer-specific methylation markers could enhance breast cancer risk assessment. We evaluated 380 women without a history of breast cancer. We determined their menopausal status or menstrual cycle phase, risk of developing breast cancer (Gail model), and breast density, and obtained… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…We enrolled 380 women with carefully documented menstrual and menopause status, and examined cumulative DNA methylation of eight genes in rFNA samples, and local breast steroid hormone concentration. We recently reported that cumulative DNA methylation of eight genes were not affected by menstrual or menopausal states, and showed significant positive associations with cytologic atypia (27). We now report on sex steroid hormone concentrations within breast tissue, its physiologic variation in a subset of 119 women, and explore relations of breast hormones with cytology, DNA methylation, and established clinical risk factors.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…We enrolled 380 women with carefully documented menstrual and menopause status, and examined cumulative DNA methylation of eight genes in rFNA samples, and local breast steroid hormone concentration. We recently reported that cumulative DNA methylation of eight genes were not affected by menstrual or menopausal states, and showed significant positive associations with cytologic atypia (27). We now report on sex steroid hormone concentrations within breast tissue, its physiologic variation in a subset of 119 women, and explore relations of breast hormones with cytology, DNA methylation, and established clinical risk factors.…”
Section: Introductionmentioning
confidence: 89%
“…We have evaluated steroid hormones in rFNA and matching blood serum samples of 119 women whose rFNA samples were collected in PBS) with ascorbic acid from our recent published study (NU 08B2; ref. 27) where 380 pre-and postmenopausal women without a breast cancer history were recruited. Data on cellularity of the rFNA sample, cytomorphology, gene methylation (cumulative methylation index, CMI), along with clinical data including lifetime Gail risk and mammographic density of this study population have been described recently (27).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations